Primary papillary epithelial tumour of the sella: expanding the spectrum of TTF‐1‐positive sellar lesions. (9th May 2020) - Roncaroli, F.; Chatterjee, D.; Giannini, C.; Pereira, M.; La Rosa, S.; Brouland, J. P.; Gnanalingham, K.; Galli, C.; Fernandes, B.; Lania, A.; Radotra, B.
Abstract : Aim: To describe four novel primary epithelial tumours of the sella with papillary architecture and Thyroid Transcription Factor 1 (TTF‐1) expression. Methods: Paraffin‐embedded tissue from the four cases and recurrence of patient 1 was investigated with haematoxylin–eosin, special histochemical stains, immunohistochemistry with a broad panel of antibodies and next‐generation sequencing. The ultrastructure of one tumour was studied in tissue retrieved from paraffin. Results: The lesions occurred in three females aged 20, 26 and 42 years and a male aged 49 years. They presented with signs and symptoms secondary to pituitary stalk compression. Preoperative neuroimaging documented mixed solid and cystic, enhancing sellar masses with suprasellar extension. Histologically, the tumours showed thin papillae lined by a single layer of cytokeratin and TTF‐1‐positive cuboidal and cylindrical cells with mildly atypical nucleus. Next‐generation sequencing performed in three cases did not identify any mutations. The main differential diagnosis included metastasis from lung or thyroid carcinoma, extraventricular choroid plexus papilloma and sellar ependymoma. Conclusion: We suggest the descriptive term of primary papillary epithelial tumour of the sella (PPETS) for this entity and propose that it could represent the intracranial equivalent of thyroid‐like low‐grade nasopharyngeal papillary adenocarcinoma. The cell of origin of PPETS remains undetermined although the intense and ubiquitous expression of TTF‐1 may suggest a derivation from the infundibulum or ventricular recess. Our study expands the spectrum of sellar TTF‐1‐positive tumour and challenges the view that they all derive from pituicytes.